Small scale electrostatically-driven aerosol deposition in airway-on-chip models of bronchial constriction - Bessler, Ron; Mekler, Tirosh; Fishler, Rami; Farhana, Oshri; Dhatavkar, Sigal; Daniel, Tamar; Kalifa, Bar; Koshiyama, Kenichiro; Korin, Netanel; Sznitman, Josué (Frontiers in Physiology, 2025)
Obstructive pulmonary diseases, including asthma and chronic obstructive pulmonary disease are widespread and represent a major global health burden. Despite their impact, effective therapeutic delivery to the small airways using inhaled aerosols remains suboptimal. In this study, we present a novel in vitro airway-on-chip platform that mimics both normal and constricted small bronchial geometries to quantify the deposition charged and neutral polystyrene latex aerosol particles ranging from 0.2 to 2 µm. Analytical and numerical solutions were derived from dimensionless scaling laws to further support the experiments and predict deposition location. Our experiments showcase how electrostatic forces significantly alter deposition patterns across particle sizes in these small airways. For submicron particles, we observe the enhancement of proximal airway deposition due to the coupling of electrostatic-diffusive screening effects. For larger particles, which typically deposit only in the direction of gravity, the inclusion of electrostatic forces significantly extends their deposition footprint, enabling deposition even in orientations where gravitational sedimentation is not feasible. Constricted regions consistently exhibit lower deposition across all cases, the presence of electrostatic forces enhanced overall deposition, offering a potential strategy for targeting bronchioles. Together, these findings suggest that electrostatic attraction may be strategically leveraged to enhance aerosol targeting in the small airways, providing new opportunities for optimizing inhaled drug delivery in obstructive lung diseases.